Maps of empire : a topography of world literature - Wanberg, Kyle, 1980- (Cultural spaces., 2020)
"During the political and historical upheavals of the mid-20th century, writers from colonized and occupied spaces questioned the necessity and ethics of their histories. Uncertainties about how to represent shifting spaces were reflected in the work of scholars and audiences reading works written by colonized peoples. As empire "wrote back" to the self-ordained centers of the world, modes of representation underwent a transformation. Exploring novels and diverse forms of literature from regions in West Africa, the Middle East, and Indigenous America, Maps of Empire examines how writers struggle with unstable boundaries generated by colonial projects and their dissolution, creating alternative topographies."--